STUDIES IN MESPILUS, CRATAEGUS, AND ×CRATAEMESPILUS (ROSACEAE), I. DIFFERENTIATION OF MESPILUS AND CRATAEGUS, EXPANSION OF ×CRATAEMESPILUS, WITH SUPPLEMENTARY OBSERVATIONS ON DIFFERENCES BETWEEN THE CRATAEGUS AND AMELANCHIER CLADES - Phipps, James B. (Phytotaxa, 2016)
The paper argues the position for retaining a monotypic Mespilus, i.e., in the sense of M. germanica, the medlar. Recent cladistic papers lend support for Mespilus being sister to Crataegus, and there is a clear morphological distinction from Crataegus, emphasized by adaptation to carnivore frugivory. Mespilus secured, the paper then treats each of the known hybrids between Mespilus and Crataegus, making the new combination Crataemespilus ×canescens (J.B. Phipps) J.B. Phipps.